2023
DOI: 10.1002/uar2.20035
|View full text |Cite|
|
Sign up to set email alerts
|

Garden soil bacteria transiently colonize gardeners' skin after direct soil contact

Abstract: Urban soils provide a number of ecosystem services and health benefits, yet they are understudied compared with agricultural and wildland soils. Healthy soils host diverse microbiota, exposure to which may be critical for immune development and protection against chronic disorders, such as allergies and asthma. Gardening represents a key pathway for microbiota exposure, yet little is known about microbial community structure of urban garden soils, degree of soil‐to‐skin transfer during gardening, nor ability o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 131 publications
0
1
0
Order By: Relevance
“…Persistent gardening results in shared, prolonged skin acquisition of soil microbiota. [141,142]. nose), Solirubrobacter (skin), and Massilia (nasal) were consistently detected after green space visits.…”
Section: Blastococcus (Skin Andmentioning
confidence: 96%
See 1 more Smart Citation
“…Persistent gardening results in shared, prolonged skin acquisition of soil microbiota. [141,142]. nose), Solirubrobacter (skin), and Massilia (nasal) were consistently detected after green space visits.…”
Section: Blastococcus (Skin Andmentioning
confidence: 96%
“…Table 4 [123][124][125][126][127][128][129][130][131][132][133][134][135][136][137][138][139][140][141][142] illustrates two fundamental principles about our connection to mi-crobes: 1) We are intimately connected to Earth's microbes, 2) Even if much of our microbiome has some stability, we are constantly exchanging microbes, microbial genes, physiologically-modifying chemicals, and gathering information from and sharing information with the microbes beyond our body. The human body is open to the environment.…”
Section: Connecting To and Through The Iom Via Meditation Embodied Co...mentioning
confidence: 99%
“…To date, only a small number of studies have examined the association between gardening and human microbiota. One study found that immediately after gardening, there is a temporary increase in the number of soil bacteria taxa that are found on the skin of the hands, but that this change diminishes over a matter of hours [16]. Another study examined the gut microbiome across the gardening season, and found increases in some bacterial taxa at the peak of gardening season [17].…”
Section: Introductionmentioning
confidence: 99%